(untitled) (Journal of the College of Education for Women, 2019)
This study aimed to identify the levels of management training in academic leaders in Jordanian universities in the north of the region and their point of view, and that by answering the following questions: 1. What levels of management training estimated by academic leaders in Jordanian universities in the territory of the North?arithmetical averages of estimates leaders academics in the territory north of the levels of management training is due to the variables of sex, job title, and the university, the type of university, academic rank, experience, and the number of courses administrative related training , and the state that got them on the last qualification? 3. What are the obstacles faced by academic leaders in the training process of the administrative point of view?To achieve the objectives of the study, the researcher has designed a questionnaire consisted of 15 items distributed on two axes, namely: First Axis: Axis levels of training is designed to Likert Pentagram. The second axis: Axis constraints faced by academic leaders in management training at Jordanian universities, and included (15) paragraph, have extended from the calibrator (1-15) by the importance of the disabled.Has been selected a random sample consisted of (118) leader academically. The study found the following results: 1. The estimates of the sample to the levels of training moderately. 2. No statistically significant differences at the level of statistical significance (α٠.٠٥ ) Estimates of academic leaders at the administrative levels of training due to all the variables of the study 3. The most significant obstacles facing academic leaders in the administrative empowerment in Jordanian universities Atsaf the university policy centralized high, weak system of rewards and incentives used at the university. Keywords: academic leaders in Jordanian universities, management training.